Tahfiz Al-Qur’an dalam Perspektif Mahasiswa Program Studi Ilmu Al-Qur’an dan Tafsir UIN Ar-Raniry Periode 2013-2015 - Furqan Amri; Suarni Suarni; Nurul Fadhilah (TAFSE: Journal of Qur'anic Studies, 2020)
This study aims to find out how the views of students of the study program of al-Qur'an and Tafsir of the year among 2013-2015 on the subject of tahfiz al-Qur'an . This research is field research using a qualitative approach that is guided by qualitative data, namely data from questionnaires, interviews, observations, and documentation. Collecting the data using a research instrument in the form of a list of questions summarized in a questionnaire and distributed to 50 samples of al-Qur'an and Tafsir students in the year among 2013-2015. Meanwhile, interviews were conducted with the caregivers for the tahfiz al-Qur'an subject. The documentation method is used to collect data about things in the form of transcripts, notes, photos, and so on and complete the data obtained from interviews or observations. The collected data is then analyzed and it shows that: All students of the Al-Qur'an and Tafsir Study Programs agree that Hifz al-Qur'an is a very important subject for this major. Among the reasons they explained was that with the existence of this Constitutional Court, it was very easy to understand the Qur'an and also study its Tafsir. Based on the results of the interviews, it can be concluded that the lecturers always provide direction regarding the methods that can be applied in memorizing the Qur'an, and the obstacles faced by students can be resolved by always approaching the Qur'an. Abstrak: Tahfiz al-Qur’an merupakan salah satu mata kuliah wajib bagi mahasiswa Program Studi Ilmu al-Quran dan Tafsir mulai dari semester pertama hingga semester lima. Dalam proses belajar mengajar, banyak mahasiswa yang menyetor hafalan kepada dosen ketika mendekati batas waktu setoran. Tulisan ini bertujuan untuk mengetahui bagaimana pandangan mahasiswa Program Studi Ilmu Al-Qur’an dan Tafsir periode 2013-2015 terhadap mata kuliah tahfiz al-Qur’an. Penelitian ini bersifat kajian lapangan dengan pendekatan kualitatif yang berpedoman pada data hasil angket, wawancara, obeservasi dan dokumentasi. Pengumpulan data melalui angket didistribusikan kepada 50 orang sampel mahasiswa Program Studi Ilmu al-Qur’an dan Tafsir periode 2013-2015, sedangkan wawancara dilakukan terhadap dosen pengasuh mata kuliah tahfiz al-Qur’an. Hasil penelitian menunjukkan bahwa seluruh mahasiswa Prodi Ilmu Al-Qur’an dan Tafsir setuju bahwa Hifz al-Qur’an adalah mata kuliah yang sangat penting bagi Program Studi ini, alasan yang mereka jelaskan adalah karena mata kuliah ini membantu mahasiswa dalam memahami al-Qur’an dan juga mempelajari Tafsirnya. Para dosen senantiasa memberikan pengarahan terkait metode-metode yang dapat diterapkan dalam menghafal al-Qur’an, dan kendala-kendala yang dihadapi mahasiswa dapat diselesaikan dengan senantiasa mendekatkan diri kepada al-Qur’an.